Warfare, political identities, and displacement in Spain and Colombia. (March 2016) - Balcells, Laia; Steele, Abbey
Abstract: This paper explores the causes of displacement during civil wars. Recent scholarship has shown that conventional civil wars – those in which forces are relatively balanced – and irregular civil wars – those in which one side is substantially stronger than the other – exhibit different patterns of violence. We hypothesize that, while the mode of violence differs, the form of displacement should be consistent across the wars: displacement is a tactic of war that armed groups use to conquer new territories. By expelling civilians associated with rivals, armed groups improve their odds of gaining control of contested territory. This implies that members of a group are targeted for displacement because of their identity and presumed loyalties. We test the theory using two fine-grained datasets on individuals displaced during a conventional civil war, in Spain (1936–1939), and an irregular civil war, in Colombia (1964–). In both cases, the war cleavage was ideological and reflected in national elections: the locations where political parties received support indicated which populations were sympathetic to rivals. In both civil wars, we observe higher levels of displacement in locations where more sympathizers of rival armed groups reside. The article is the first comparison to our knowledge of the sub-national dynamics of displacement within two different civil wars and it shows that the microfoundations of displacement are similar across types. Finally, the article explains macro-level differences with a coherent micro-level framework.